Chip-based digital PCR as a novel detection method for quantifying microRNAs in acute myocardial infarction patients. (July 2018) - Robinson, Samuel; Follo, Marie; Haenel, David; Mauler, Maximilian; Stallmann, Daniela; Heger, Lukas Andreas; Helbing, Thomas; Duerschmied, Daniel; Peter, Karlheinz; Bode, Christoph; Ahrens, Ingo; Hortmann, Marcus
Abstract miRNAs have shown promise as potential biomarkers for acute myocardial infarction (AMI). However, the current used quantitative real-time PCR (qRT-PCR) allows solely for relative expression of nucleic acids and it is susceptible to day-to-day variability, which has limited the validity of using the miRNAs as biomarkers. In this study we explored the technical qualities and diagnostic potential of a new technique, chip-based digital PCR, in quantifying the miRNAs in patients with AMI and ischaemia-reperfusion injury (I/R). In a dilution series of synthetic C.elegans-miR-39, chip-based digital PCR displayed a lower coefficient of variation (8.9%vs 46.3%) and a lower limit of detection (0.2 copies/μLvs 1.1 copies/μL) compared with qRT-PCR. In the serum collected from 24 patients with ST-elevation myocardial infarction (STEMI) and 20 patients with stable coronary artery disease (CAD) patients after percutaneous coronary intervention (PCI), we used qRT-PCR and multiplexed chip-based digital PCR to quantify the serum levels of miRNA-21 and miRNA-499 as they have been validated in AMI in prior studies. In STEMI, I/R injury was assessed via measurement of ST-segment resolution (ST-R). Chip-based digital PCR revealed a statistical significance in the difference of miR-21 levels between stable CAD and STEMI groups (118.8 copies/μLvs 59 copies/μL;P =0.0300), whereas qRT-PCR was unable to reach significance (136.4 copies/μLvs 122.8 copies/μL;P =0.2273). For miR-499 levels, both chip-based digital PCR and qRT-PCR revealed statistically significant differences between stable CAD and STEMI groups (2 copies/μLvs 8.5 copies/μL, P =0.0011; 0 copies/μLvs 19.4 copies/μL;P <0.0001). There was no association between miR-21/499 levels and ST-R post-PCI. Our results show that the chip-based digital PCR exhibits superior technical qualities and promises to be a superior method for quantifying miRNA levels in the circulation, which may become a more accurate and reproducible method for directly quantifying miRNAs, particularly for use in large multi-centre clinical trials.